ANÁLISIS DE LOS FACTORES QUE IMPIDEN A LOS PROFESIONALES DEL TURISMO DE LA UTB, EL DESARROLLO DE EMPRENDIMIENTOS TURÍSTICOS - CEREZO HUAYAMAVE, KENYI LEONELA (2024)
The present study deals with the analysis of the factors that prevent tourism professionals from the UTB, the development of tourism ventures in the tourism graduate students of the Technical University of Babahoyo, a qualitative type of research was used by applying a survey to collect sample data from 11 graduates in different periods of the Technical University of Babahoyo, which was very useful, 80% were female and 20% male, in an age range of 20 to 25 years it is determined that some of The main factors are lack of financing, limited training, experience limitations, weak institutional support, and risk cultures. There are few who have a business but in the tourism sector. Strategies are proposed to overcome obstacles, such as creating a variety of training programs, developing business incubations and promoting entrepreneurship. The study concludes that the development of entrepreneurship for UTB tourism graduates is a medium level due to the factors already mentioned.